Native and pegylated forms of L-asparaginase: the assessment of effectiveness and toxicity in acute lymphoblastic leukemia treated with Berlin–Frankfurt–Munster (BFM) protocol - M. A. Shervashidze; D. S. Smirnova; T. T. Valiev; N. A. Batmanova (Онкогематология, 2024)
Background. L-asparaginase is an integral part of chemotherapy regimens in treatment of patients with acute lymphoblastic leukemia (ALL). However, the use of L-asparaginase is limited due to wide range of adverse reactions. Our research demonstrates the toxicity effects and treatment results in patients with ALL who received native and pegylated (EG) L-asparaginase.Materials and methods. From 2013 to 2023 in the study 199 patients with newly diagnosed ALL were enrolled. Patients were treated according to the ALL IC-BFM 2009 protocol including L-asparaginase. The average age of patients was 4.6 (1–18) years. B-ALL was diagnosed in 175 (87.9 %) patients, T-ALL in 24 (12.1 %) patients. Native L-asparaginase was used in the therapy of 51 (25.6 %) patients; if allergic reactions occured, 72 (36.2 %) patients received EG asparaginase. In 76 (38.2 %) patients treatment protocol included only EG-asparaginase without native L-asparaginase history.Results. The most common adverse event was a hypersensitivity reaction – 27.6 % (n = 55), which was more common in the cohort of patients receiving native L-asparaginase. The incidence of hypercoagulation for patients treated with native L-asparaginase was 4 % and 0 % – for EG-asparaginase group. Hypocoagulation, presented as hypofibrinogenemia registered in 13 % of patients received native L-asparaginase and in 35 % for EG-asparaginase group. ancreatitis, complicated ALL treatment were diagnosed in 4 % after native L-asparaginase and 1 % after EG-asparaginase. The best 5‑year survival rates were observed in the group of patients who initially received EG-asparaginase – overall and eventfree survival were 100 and 87.5 (11.7) %, respectively (р >0.05).Conclusion. Despite the absence of convincing survival benefit in patients with newly diagnosed ALL treated with EG-asparaginase, the toxicity profile was better in contrast to native L-asparaginase.